Shock associated with endothelial dysfunction in omental microvessels. (7th December 2016) - Somberg, Lewis B.; Gutterman, David D.; Miura, Hiroto; Nirula, Raminder; Hatoum, Ossama A.
Abstract: Background: Impaired microvascular function leads to a poor outcome in a variety of medical conditions. Our aim was to determine whether vasodilator responses to acetylcholine (Ach) are impaired in human omental arterioles from patients with severe trauma. Materials and methods: Patients with massive blood loss and severe shock requiring damage control procedures were included. Tissues were collected at the first (FEL) and the second explorative laparotomy (SEL). Control tissues were collected from nontrauma patients. Freshly isolated 50–200‐μm‐diameter omental arterioles were analysed using videomicroscopy. Dihydroethidine and DCF‐DA fluorescence were used to assess reactive oxygen species (ROS) production. MnTBAP was used to determine the contribution of excess vascular superoxide contribution to endothelial dysfunction. Results: After constriction (30–50%) with endothelin‐1, dilation to graded doses of Ach (10 −9 –10 −4 M) was greater in control vessels compared to FEL and SEL (max dilation at 10 −4 M (MD) = 25 ± 3%, n = 8; and 59 ± 8%, n = 8, respectively, and controls MD = 93 ± 10%, n = 6, P < 0·05). Fluorescence imaging of ROS production showed significant increases in superoxide (225·46 ± 12·86; 215·77 ± 10·75 vs. 133·75 ± 7·26, arbitrary units; P < 0·05) and peroxide‐related ROS (240·8 ± 20·42; 234·59 ± 28·86, vs. 150·78 ± 15·65, arbitrary units; P < 0·05), in FEL and SEL microvessels compared to control, respectively. FEL pretreated with MnTBAP demonstrated significant improvement in Ach‐induced vasodilation (25·5 ± 3·0% vs. 79·5 ± 8·2%; P < 0·05). Conclusions: Severe shock associated with microvascular endothelial dysfunction enhances production of ROS in human omental tissues. The altered flow regulation may contribute to a mismatch between local blood supply and demand, exacerbating abnormal tissue perfusion and function.